DEVELOPMENT OF MANGROVE ECOTOURISM IN RAWA MEKAR JAYA VILLAGE SIAK REGENCY RIAU PROVINCE - Rohadatul Aisy; Dessy Yoswaty; Musrifin Galib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT            This research was conducted in February – March 2019 in Rawa Mekar Jaya Village, Siak Regency, Riau Province. The purpose of this study was to determine the potential of mangrove ecosystems, to know the level of participation and perseption of the stakeholder. The method used was the survey method. The results showed that the mangrove forest in Rawa Mekar Jaya Village has the potential to be a mangrove ecotourism area and has a diversity of flora and fauna. The level of community participation in the development of mangrove ecotourism in Rawa Mekar Jaya Village is high, while the level of public perception is classified as supporting the medium category. This means that the community strongly agrees if their area is developed as an ecotourism area and has a positive impact both ecologically and economically. Keywords: Ecotourism, Mangrove, Participation, Perception, Rawa Mekar Jaya Village